A molecular phylogenetic study of Clarohilum henningsii (Mycosphaerellaceae, Fungi) on cassava from Indonesia based on the ITS rDNA sequence - Iman Hidayat; Aerma Hastuty; Indriati Ramadhani (Microbiology Division, Research Center for Biology, Indonesian Institute of Sciences, 2020)
Leaf spot is a common disease of cassava in Indonesia and other tropical countries. The present study aims to determine two isolates isolated from leaf spot of cassava in Indonesia using a molecular phylogenetic analysis based on internal transcribed spacer (ITS) rDNA sequence and morphological examination. The results showed that the two isolates belong to Clarohilum henningsii. This study revealed the phylogenetic position of C. henningsii from Indonesia, where in the previous studies, it has been reported as Cercospora cassavae, C. manihotis, C. henningsii, or Passalora henningsii based on morphological examinations.